Organização e uso das bases de informação para o atendimento a clientes em call centers - Sandra Maria Silveira (2006)
This study opens the discussion on customer support service within the scope of Information Sciences and seeks to understand the phenomenon under the lens of Organization and Use of Information. To this end, its general objective is to analyze the informational process of customer support services rendered at call centers, with a focus on the organization and use of information bases, considering the systematization of parameters that provide subsidies to the creation, maintenance, and validation of customer service scripts. Its specific objectives are: to put customer support service into context within the framework of institutions inside information societies; to characterize customer support service within the context of a specialized information service; to characterize the use of support script bases as the source of information for customer support service; to characterize and verify the information organization processes that provide input for the creation, maintenance, and validation of information bases; to identify information quality attributes that lead to the construction and maintenance of information bases; and to systematize parameters to design information bases in accordance with processes for organizing and using information within the scope of Customer Support Services. In order to reach these goals, the fields with the greatest rate of customer complaints were identified within the services sector, a central activity in the Information Society. Semi-structured interviews were carried out with institution officers and information managers, and questionnaires were presented to the Customer Support Personnel at the three institutions that were researched: a bank, a health care firm and a mobile communications company. To obtain the point-of-view of clients on this information service, a semi-structured interview was carried out with a representative from the governments consumer rights agency PROCON in the city of Belo Horizonte. The theoretical discussion sets the services and units of information, as well as the processes by which information is organized and used, within the scope of call centers; it also seeks to clarify, under the lens of Information Theory, the informational process which takes place at Customer Support Centers. The connection of technical studies with empirical research gave way to the draft of a proposal for a technical norm for organizing information to create and maintain script bases for customer support.